3(2x+1)=5(x-4)

Simple and best practice solution for 3(2x+1)=5(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+1)=5(x-4) equation:


Simplifying
3(2x + 1) = 5(x + -4)

Reorder the terms:
3(1 + 2x) = 5(x + -4)
(1 * 3 + 2x * 3) = 5(x + -4)
(3 + 6x) = 5(x + -4)

Reorder the terms:
3 + 6x = 5(-4 + x)
3 + 6x = (-4 * 5 + x * 5)
3 + 6x = (-20 + 5x)

Solving
3 + 6x = -20 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
3 + 6x + -5x = -20 + 5x + -5x

Combine like terms: 6x + -5x = 1x
3 + 1x = -20 + 5x + -5x

Combine like terms: 5x + -5x = 0
3 + 1x = -20 + 0
3 + 1x = -20

Add '-3' to each side of the equation.
3 + -3 + 1x = -20 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = -20 + -3
1x = -20 + -3

Combine like terms: -20 + -3 = -23
1x = -23

Divide each side by '1'.
x = -23

Simplifying
x = -23

See similar equations:

| 5(b-6)=3(b+4) | | x+y=4x | | 3(3-x)=15x-27 | | -5y+-5(6-2y)=0 | | 15x-10=-9x+3 | | lny=-3ln(x)+ln(C) | | 4-8x-x=-23 | | 3a^2+25a+50=0 | | 8q-5=5q+3 | | 2y+y-.5=23.5 | | 11-9=-23 | | X+6*4=126 | | 8x=4x-6 | | .4x^2+.2=x | | x-6-7=26(x-7) | | -8x-x=99 | | 6n+2=n+8 | | 2(9c-6)=14 | | -4m-2=82 | | -8(n-7)+3(n-3)=41 | | (9x+y)+(3x+2y)=180 | | -8(n-7)+3(n-3)=31 | | 64=8w-8 | | 2N+7(9N+10)= | | 6+.010x=0.15x+8 | | 4p+2=p+4 | | -5y-5(-62y)=0 | | 13.33+.11x=13.83+.08x | | 14a+5=33 | | -8(b+2)=32 | | 3.25x+5.50y=112.4 | | 93=2x-3(-2x-7) |

Equations solver categories